Papers from the CCI Conference on Communications 2006 - Goodman, Michael B. (Corporate communications, 2007)
This e-book draws on papers presented at the 2006 Corporate Communication Institute Conference at Wroxton College, UK. The aim of the conference was to illuminate the interest in corporate communication as a strategic function in organizational success; explore the influence of globalization on the corporate communication profession; and to provide a forum for the exchange of ideas and information. The 6 papers chosen for the special issue reflect these objectives as they encompass a broad scope covering issues like corporate slogans in Greater China, the expression of Corporate Social Respons.